The Role of COVID-19 in Excess Mortality in Slovakia: A Novel Approach Based on Healthcare Billing Records - Barančok, Peter; Dudek, Ján; Ištokovičová, Petra; Kandilaki, Daniela; Kotrč, Michal; Löffler, Ľubica; Mišík, Matej; Mužik, Roman; Saal, Beáta; Vrbiková, Martina; Zajac, Rudolf; Selvek, Martin; et al. (International journal of public health, 2024)
OBJECTIVES: Propose a methodology to identify COVID-19 associated deaths using healthcare billing records and evaluate its effectiveness by comparing the results with excess mortality data from 2020 to 2022 and confirmed COVID-19 deaths. METHODS: A retrospective quantitative analysis was conducted by merging healthcare billing records with cause of death data. The term "COVID-19 associated death" was defined as any death occurring within a defined timeframe following a confirmed contact with COVID-19. This category includes individuals who died directly due to COVID-19, with COVID-19 as a contributing factor, or as an aftermath of a COVID-19 infection, as well as those who died from other causes but had previously contracted COVID-19. This broader definition provides a more comprehensive measure of excess mortality compared to the officially confirmed COVID-19 deaths attributed to the virus. RESULTS: We identified 35,399 COVID-19 associated deaths during the 3-year pandemic in Slovakia compared to 21,395 confirmed COVID-19 deaths. CONCLUSION: The identification of COVID-19 associated deaths with our methodology offers a more accurate explanation for the notably high excess mortality observed in Slovakia (31,789 deaths) during the pandemic, relative to the EU27. Given the high level of excess mortality, the officially confirmed deaths are likely underestimated, and the presented methodology provides a more precise measure of mortality. Additionally, healthcare billing records prove valuable in identifying these deaths at the individual patient level using claims data of health insurance companies, which is crucial for implementing targeted preventive measures and improving preparedness for future pandemics.
Keywords: dospělí; Female; SARS-CoV-2; Cause of Death; Adult; ženské pohlaví; Slovakia; lidé; COVID-19; pandemie; retrospektivní studie; Male; Aged; lidé středního věku; Slovenská republika; senioři; mužské pohlaví; příčina smrti; Retrospective Studies; Pandemics; Middle Aged; Humans